PENGARUH KURS, KONSUMSI PEMERINTAH DAN NET FOREIGN ASSET TERHADAP NERACA PERDAGANGAN DI NEGARA-NEGARA ASEAN - Queen Shinta Dewi; Taufiq Carnegi Dawood; Rustam Effendi; Muhammad Ilhamsyah Siregar; Muhammad Abrar; Fitriyani Fitriyani (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2021)
AbstractThis study objective is to analyze the factors which affect the trade balance in ASEAN countries. The data in this study uses secondary data in the form of annual data from 1990 to 2019 obtained from the World Bank, FRED, CEIC, andthe Ministry of Finance. The method employed is the GLS random effect panel data analysis model. The conclusion of this study is that the exchange rates, government consumption and Net Foreign Assets have a significant and positive effect on the trade balance of ASEAN countries.